Acceptability of Covid-19 Vaccine Informations to Health Consciousness Tourism Industries in Bandung City - Irwanto Irwanto; Dina Andriana; Widarti Widarti; Jusuf Fadilah; Laurensia Retno Hariatiningsih (Budapest International Research and Critics University, 2022)
This research reveals as well as examines the relationship between the acceptability of Covid-19 vaccine information on health awareness in the tourism industry sector in the city of Bandung. This city is one of the tourist destinations that must rise from adversity due to Covid-19. The vaccine program was launched by the government to attract tourists again. The approach to answering this research uses a positivistic paradigm with quantitative research techniques. The validity and reliability test using SPSS was carried out on 85 respondents from a population of 300. A strong relationship was found between the acceptability of the Covid 19 vaccine information and the health awareness of tourism sector business actors in the city of Bandung. They were positive to receive information about the Covid vaccine to run their business. This study also found that respondents received vaccine information based on the purpose so that their business could run. It was also revealed that respondents were not sure with certainty that they could carry out the vaccine process. Furthermore, significant data were found that respondents were less active in seeking information about health.